Evaluasi Penerapan Ijob Isafety Ianalysis Idan Istandard Operational Procedure Ipada Ipenambangan Ibatu Igamping Ipt. Anugrah Ihalaban Sepakat, Ikabupaten Ilimapuluh Ikota, Sumatera Barat - Farhan Dwi Almukharabi; Fadhilah Fadhilah (Journals Mining Engineering : Bina Tambang, 2022)
PT. Anugrah iHalaban iSepakat iis ia ilimestone imining icompany iwhich iis ilocated iin iLaharkumbuh, ififty icities. iPT. iAnugrah iHalaban ihas iagreed ito iimplement ioccupational isafety iand ihealth i(K3) iin imining iactivities, ibut ithe iimplementation iis istill inot ioptimal. iThis iis idue ito ithe inon-optimal iuse iof ipersonal iprotective iequipment i(PPE), isome iworkers iwho ido inot icomply iwith icompany iregulations, ithe ioccurrence iof iwork iaccidents, ithe ineed ifor irepairs iand iadditions ito ithe irequired iJSA iand iSOP. iThe iresults iof ithe iquestionnaire ianalysis iof ithe ievaluation ilevel iof ithe iimplementation iof iJSA iand iSOP ion ithe ioperation iof iexcavators, idump itrucks iand icrushers ias ia iwhole iat iPT. iAnugrah iHalaban iagreed ithat ibased ion ithe iLiker iscale icalculation, ithe iJSA ivalue iwas i86% iand ithe iSOP iwas i86%. iWith ithe icriteria ifor ithe iJSA ivalue ifor iexcavator ioperation i88% iand iSOP i89%, ithe iJSA ivalue ifor idumptruck ioperation iwas i87% iand iSOP i86%, ithe iJSA ivalue ifor icrusher ioperation iwas i78% iand iSOP i82%. iThe ifrequency iof iaccidents iin i2021 iwas i10.41 iwithout ilosing iwork idays iand iwork iaccidents iin imining iareas ioccurred i3 i(three) itimes. iImprovements iand iadditions ito iJSA iand iSOPs icarried iout ion iexcavator, idumptruck iand icrusher ioperation iactivities.